RAS-inhibiting biologics identify and probe druggable pockets including an SII-α3 allosteric site - Katarzyna Z. Haza (Nature Portfolio, 2021)
Oncogenic RAS mutants remain difficult to target with small molecules. Here, the authors show that RAS-binding Affimer proteins inhibit RAS signaling while binding diverse regions on the RAS surface, suggesting the potential to use Affimers as tools to identify new binding pockets and pharmacophores.